Prenatal methamphetamine hydrochloride exposure downregulates miRNA-151-3p and CACNA1C in testis rats’ offspring: MiRNA-151-3p and CACNA1C downregulated by METH - Bakhshaei, Romina; Zare, Nayere; Baghi Zadeh, Zahra; Ghorbani Yekta, Batool (Cellular and Molecular Biology, 2024)
Due to the widespread use of methamphetamine (METH) among reproductive-aged women, the effects of intrauterine exposure to METH need to be investigated, as previous studies on this topic have been limited. The goal of this study is to examine the influence of two regulatory genes (miRNA-151-3p and CACNA1C) on the intrauterine life of mice exposed to METH. Pregnant mice received doses of 2 and 5 mg/kg of METH and saline from day 10 of pregnancy until the end. Their offspring were then evaluated for miRNA-151-3p and CACNA1C gene expression levels using real-time PCR. The findings indicated that exposure to METH reduced the expression levels of both miRNA-151-3p and CACNA1C genes in offspring compared to the control group (p≤0.001). In conclusion, intrauterine exposure to METH leads to a decrease in expression levels of both miRNA-151-3p and CACNA1C genes, potentially disrupting regulatory pathways involving these genes and having an impact on male reproductive health.